Fbw7 regulates apoptosis in activated B-cell like diffuse large B-cell lymphoma by targeting Stat3 for ubiquitylation and degradation. Issue 1 (December 2017) - Yao, Su; Xu, Fangping; Chen, Yu; Ge, Yan; Zhang, Fen; Huang, Huijie; Li, Li; Lin, Danyi; Luo, Xinlan; Xu, Jie; Luo, Donglan; Zhu, Xiaolan; et al.
Abstract Background The ubiquitin-ligase Fbw7 acts as a tumor suppressor, targeting lots of proto-oncogenes for proteolysis. However, the exact role of Fbw7 in diffuse large B-cell lymphoma (DLBCL) development remains unclear. Methods We evaluated Fbw7 expression in patient samples of DLBCL using immunohistochemical staining. The effect of Fbw7 overexpression on cell viability and apoptosis was investigated using activated B-cell (ABC) like DLBCL cell lines. The mechanism of Fbw7 activity in DLBCL was investigated using immunoprecipitation, ubiquitination, western blot and qualitative analyses. Results The non-germinal center B-cell-like subtype of DLBCL showed reduced Fbw7 expression compared with the germinal center B-cell (GBC) subtype, and low Fbw7 expression was associated with a worse prognosis. Fbw7 overexpression caused decreased cell viability and increased apoptosis rates in the ABC-DLBCL cell lines SU-DHL-2 and OCI-LY-3. Importantly, Stat3 and phospho-Stat3Tyr705 stability were reduced following Fbw7 overexpression in ABC-DLBCL cell lines. In HEK293T and SU-DHL-2 cells, we demonstrated that Fbw7 interacts with Stat3 and pStat3Tyr705 to regulate their ubiquitylation and degradation. Downstream anti-apoptotic target genes of activated Stat3, including Myc, Survivin, Mcl-1, Pim-1, Bcl-2 and Bcl-xl showed decreased mRNA expression following exogenous Fbw7 overexpression. The negative relationship between Fbw7 and pStat3Tyr705 levels was also confirmed in DLBCL patient samples. Conclusion The ubiquitin-ligase Fbw7 mediates apoptosis through targeting Stat3 for ubiquitylation and degradation in ABC-DLBCL. Thus, our study may offer a promising approach for ABC-DLBCL therapy through Stat3 inhibition.